EFEKTIVITAS PLYOMETRIC TRAINING TERHADAP KEMAMPUAN KECEPATAN PADA PEMAIN BASKET: Literature Review - Corry Rakhel Artania (2020)
Sprint ability on basketball players play an important role in basketball, because during the turns the players have to run away, maybe for offensive and defensive structures. To support the ability of sprint in basket players takes optimal training of these abilities. So plyometric training based on existing research says this exercise with a dose adjusted to the age of the player can improve the sprint ability of the basketball players. The purpose of this study is to find out the effect of plyometric training on sprint ability on basketball players. The method of selecting literature uses Google Schoolar and ReserchGate sources as well as sorting based on source inclusion criteria by reading abstracts and filtering the literature. The results one of this literature show a significant value that is p <0.05 Running 20 meters CG 4.46 ± .42 4.19 ± .43 3,090 0.013 * PG 4.56 ± .76 4.13 ± .39 2.724 0.023 *. Summary of plyometric exercises influence on Increasing the basketball player's sprint ability.